Is 360-degree feedback related to organizational success? An empirical contribution in the Italian context Il feedback a 360° è collegato al successo lavorativo? Un contributo di ricerca nel contesto italiano - Dello Russo, S.; Santarpino, M. M.; Borgogni, L.; Signori, A. (Counseling: Giornale Italiano di Ricerca e Applicazioni, 2014)
The present study aims to contribute to the research on 360-degree feedback by investigating inter-rater agreement and the predictive validity of different rating sources. The sample consisted of 35 managers from an Italian manufacturing firm in the automotive sector. Each manager was assessed by him- or herself, the supervisors, the colleagues and the co-workers. An average of 14 evaluations was received. A questionnaire which tapped five broad domains of competence was used to gather data. Results showed that self-evaluations did not correlate positively with any other sources. However, colleagues’ evaluations correlated positively with those provided by supervisors and co-workers. Furthermore, colleagues’ evaluations were the only significant predictors of ratees’ subsequent goal achievement. The practical implications of these findings are discussed, along with future research perspectives.